2019
DOI: 10.1584/jpestics.d18-011
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and expression level of <i>CYP51</i> (cytochrome P450) and sensitivity to ipconazole in <i>Fusarium fujikuroi</i> isolates

Abstract: The relationship between the nucleotide sequences of CYP51, its expression level and its sensitivity to ipconazole of Fusarium fujikuroi isolates were investigated. Single nucleotide polymorphisms (SNPs) were observed in the CYP51 of isolates with different sensitivities to ipconazole, but no amino acid substitution was detected in the putative amino acid sequence of the CYP51 protein. On the other hand, the expression of CYP51 was enhanced by the presence of ipconazole, and it tended to be higher in isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Type I resistant isolates (half of the resistant isolates) were found with no insertions in the promoter region, consistent with results from Sclerotinia homoeocarpa 41 and Fusarium fujikuroi. 42 Type II resistant isolates (the other half of the resistant isolates) were observed to contain a 6 bp insertion in the promoter region, which may be associated with DMI resistance but needs further verification. However, it is unknown whether transcription factors 43 or CYP51 copies 44 contribute to the over-expression of CYP51 in our resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I resistant isolates (half of the resistant isolates) were found with no insertions in the promoter region, consistent with results from Sclerotinia homoeocarpa 41 and Fusarium fujikuroi. 42 Type II resistant isolates (the other half of the resistant isolates) were observed to contain a 6 bp insertion in the promoter region, which may be associated with DMI resistance but needs further verification. However, it is unknown whether transcription factors 43 or CYP51 copies 44 contribute to the over-expression of CYP51 in our resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that induced expression of CYP51 was associated with DMI resistance in all resistant isolates with two genotypes. Type I resistant isolates (half of the resistant isolates) were found with no insertions in the promoter region, consistent with results from Sclerotinia homoeocarpa and Fusarium fujikuroi . Type II resistant isolates (the other half of the resistant isolates) were observed to contain a 6 bp insertion in the promoter region, which may be associated with DMI resistance but needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors inhibited the activity of these enzymes and blocked the synthesis of ergosterol, which may disrupt the structure of the cell membrane and prevent infection and reproduction. CYP51 is an important enzyme in the biosynthetic process of ergosterol, and DMIs target CYP51 enzymes [ 59 ], e.g., CgCYP51A and CgCYP51B in C. gloeosporioides [ 60 ]. Here, we characterized the role of CsCyp51G1 in regulating the sensitivity of C. siamense to fludioxonil but not azoles.…”
Section: Discussionmentioning
confidence: 99%
“…G-group/bakanae type strains produce GAs but no or low FUM, while F-group/stunt type strains produce FUM but no or low levels of GAs [22,23]. Interestingly, different sensitivities to the fungicides thiophanate-methyl [22] and ipconazole [24] were observed between the G-group and F-group strains. Despite the development of management strategies, F. fujikuroi still causes bakanae disease worldwide.…”
Section: Introductionmentioning
confidence: 94%